IMPLEMENTASI REALISTIC MATHEMATICS EDUCATION (RME) BERBANTUAN VIDEO ANIMASI MATERI PENGUKURAN TIDAK BAKU TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA SEKOLAH DASAR - Aprilia, Della; Alexander Alim, Jesi; Hainul Putra, Zetra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low ability to understand mathematical concepts of elementary school students, especially in non-standard measurement material. This problem is caused by learning that is still conventional and the lack of use of conceptual and interesting learning media. This research aims to analyze the effect of implementing Realistic Mathematics Education (RME) assisted by animated videos on elementary school students' ability to understand concepts. This research uses a quantitative approach with a quasi-experimental method and a Nonequivalent Pretest-Posttest Control Group design. The subjects of this research consisted of 40 class I students at SDN 188 Pekanbaru who were divided into experimental classes and control classes. Data collection techniques use tests, observation and documentation. Data analysis was carried out through normality test, homogeneity test, independent sample t-test, and N-Gain test. The research results show that there is a significant influence with a significance value of 0.049 <0.05. The post-test average for the experimental class was 70, while the control class was 57.5. The N-Gain test results showed an increase in the experimental class of 0.42 in the medium category and the control class of 0.17 in the low category. Thus, the implementation of RME assisted by animated videos on non-standard measurement material is quite effective in improving the conceptual understanding ability of class I students at SDN 188 Pekanbaru.